THE EFFECT OF MANAGING RISK PROCESS IN CONSTRUCTION PROJECTS - Kaka HamaAttar, Khanm Noori (International Journal of Engineering Technologies and Management Research, 2018)
The aim of this study is to get a better understanding for the effect of the set of the risks in the construction projects, in addition to how mitigating these risks in those projects. Indeed risks are frequently playing the same rules, but the nature of project defines the specific risks of the project. The first step in process of risks assessment is identification them. Once risk identification is complete, risk analysis is used to identify the likelihood the risks that have been identified will happen. Thus by using evidence from other research in the area, this study showed the impact of the set of the stages in the risk management process in the construction projects, which were discussed in greater detail in the theoretical aspect of the current study. The findings of the study were revealed the fact that the comprehension of risk and its management has the direct effect of understanding specific issues that involve to the project. In addition to that, the integration of a risk management process at each stage of its stages in construction projects must be oriented to the progress of the project and permeate all areas, functions and processes of the project. In this regard, the most successful project managers maintain open lines of communication throughout their organizations to stay in touch with constituent’s needs.